Prospective Study of Biliary Strictures to Determine the Predictors of Malignancy - Vincent G Bain; Neena Abraham; Gian S Jhangri; Tim W Alexander; Ron C Henning; Michael E Hoskinson; Conor G Maguire; Eoin AG Lalor; Daniel C Sadowski (Canadian Journal of Gastroenterology)
BACKGROUND: There have been few prospective studies regarding the investigation of biliary strictures, principally because of rapid technological change. The present study was designed to determine the sensitivity of various imaging studies for the detection of biliary strictures. Serum biochemistry and imaging studies were evaluated for their role in distinguishing benign from malignant strictures.